2022
DOI: 10.21037/apm-22-422
|View full text |Cite
|
Sign up to set email alerts
|

Learning about psychiatric aspects of medical assistance in dying: a pilot survey of self-perceived educational needs among assessors in a Canadian academic hospital

Abstract: Background: Medical assistance in dying (MAiD) was legalized in Canada in 2016, although it has been accessible as an end-of-life option in the province of Quebec since 2015. Before its implementation in clinical settings, few physicians had received formal training on requests assessments. New data indicate MAiD requesters have high rates of psychiatric comorbidities. Hence, assessment and management of psychiatric and psychosocial issues among MAiD requesters are important competencies to develop for assesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 6 , 15–18 Preliminary data revealed that assessors are interested in further training on psychiatric aspects. 19 Centering MAiD on the patient's needs remains a complex task. 20 …”
Section: Patients-partners' Contribution To Educational Challengesmentioning
confidence: 99%
“… 6 , 15–18 Preliminary data revealed that assessors are interested in further training on psychiatric aspects. 19 Centering MAiD on the patient's needs remains a complex task. 20 …”
Section: Patients-partners' Contribution To Educational Challengesmentioning
confidence: 99%
“…The study by Rivest et al must face the possible limitation of selection bias with regard to its small sample size of 19 participants, which might have a favourable opinion towards MAiD (7). However, the response rate of the survey was high and seemed to be representative of an attitude among Canadian physicians that MAiD has become part of medical practice.…”
mentioning
confidence: 99%
“…Rivest et al's study results revealed that Canadian physicians reported high levels of competency in managing psychiatric issues among MAiD requesters (7). The authors concluded that this may indicate overconfidence among the participants, as 95% of the participants reported providing EOL care on a regular basis, while 47% had never received any PC or EOL training (7). The authors stated that there is still very little postgraduate training on psychiatric symptoms in PC.…”
mentioning
confidence: 99%
See 2 more Smart Citations